THE ROLE OF MIRNAS IN TYMORIGENESIS.LITERATURE REVIEW. - I.S. Brodetskyi (Ukrainian Medical Stomatological Academy, 2019)
Introduction. There are many diagnostic techniques in modern medicine, that enable preoperative and postoperative human neoplasms verification (identification).There are a number of postoperative diagnostic techniques, namely his to pathological, immunohistochemical and genetic one. The last-mentioned is rather popular. One of the genetic approaches in tumor diagnostics is the examination of the role of microRNA molecules. The aim of our work is to reveal the role of microRNA molecules on tumor genesis in accordance with the literature review. Research findings.A microRNA is a small non-coding RNA consisting of approximately 22 nucleotides andit is found in all eukaryotic cells. Up to now, we know about 2588 microRNAs. The review of the majority of literature sources has shown, that microRNA molecules may impact on significant biological processes: cell cycle control, apoptosis, metabolism, cellular development and differentiation along with the development of the wide range of diseases: neurodegenerative, metabolic disorders and cancer. Furthermore, they may regulate carcinoma-dependent processes - proliferation, apoptosis, migration, invasion, play a crucial role in stem cells differentiation and control cancer stem cells formation and obtaining of the epithelial-to-mesenchymal transition phenotype, which is directly connected with drug resistance. Using of microRNA profiles we can differentiate sound and cancer tissues, identify the tissue`s origin and distinguish different subtypes of certain cancer or even specific oncogenic deviations (abnormities) and prognosticate the result or response to therapy. Nowadays, its usage in human neoplasms diagnostics made it possible to create a promising area in malignant tumor treatment that in addition to chemotherapy extends lifespan of oncology patients. And the examination of the role of microRNA on such processes as apoptosis and interaction with cytokines makes it possible to know about new mechanisms of pathogenesis in the development of the majority of tumors and particularly salivary gland tumors (pleomorphic adenomas). The ability of the microRNA identification in various biological fluids (blood, saliva) allows us to receive further information regarding one or another pathology and the examination of tumor biopsy for the presence of these markers helps us to increase the probability of tumor verification. Treatment development with usage of exosomal microRNA for the regeneration of damaged organs of an adult offers new opportunities in the therapy of various diseases. Conclusions. Thus, genetic tumor research methods (microRNA) are an advanced technology that allows us to increase tumor identification, to make an impact on different biological processes, to differentiate and classify the most of tumors of the body, and to adopt state-of-the-art medicines and prognosticate the result or response to therapy.